Professional Skills in Journalism: a Comparative Evaluation - Casero-Ripollés, Andreu; Ortells-Badenes, Sara; Doménech-Fabregat, Hugo (Historia y Comunicación Social, 2014)
The aim of this paper is to analyse which are the formative skills linked to journalism that have worthier value recognition for two groups: students and professionals of the sector. The methodology is based on a quantitative survey. The sample consists of 126 students from different courses of the Journalism Degree at the Universitat Jaume I of Castellón and 30 professionals working in different mass media. Results show that, despite of the crisis, both groups still trust in a future employment market linked to the traditional media, showing a limited entrepreneurship vision.